Evaluation of the Bologna Process in Sulaimani University from the perspective of students - ابراهیم, م.م. شاڵاو عبداللە ابراهیم; قادر, م.م.ئالان عمر قادر; حمد, م.م.هێژا عبداللە حمد (Sulaimani Journal for Humanities, 2025)
This research aims to evaluate the Bologna Process implementation at the University of Sulaymaniyah from the students' perspective and to determine the level of Bologna Process awareness according to gender, place of residence, and college variables for the academic year)2024-2025(The research population consists of all students at the University of Sulaymaniyah, totaling) 20,715(students. The research sample comprises) 1,022(students, including) 452(female students and)570(male students, selected through simple random sampling. The researcher employed a descriptive methodology appropriate to the nature of the study. In addition to utilizing previous research and other sources, the researcher developed a survey questionnaire to measure the evaluation of the Bologna Process at the University of Sulaymaniyah, consisting of )29(items. To ensure the validity and appropriateness of the instrument, the researcher conducted validation procedures with a number of experts and specialists in teaching methods, education, and psychology. The questionnaire was subsequently administered to the main research sample, and the researcher proceeded to collect and analyze student responses using SPSS (Statistical Package for the Social Sciences) software to present the research findings. Finally, the researchers reached a set of conclusions, recommendations, and suggestions based on the study findings.
Keywords: Assessment; Bologna; Process; University; Student